RANCANG BANGUN APLIKASI TRACKING BERBASIS WEBSITE PADA PT ABCDE - Akbar Bintang Izzulhaq; Ananda Azizul Akbar; Rizky Firman Setya Putra; Alif Firdiansyah; Endra Rahmawati (LPPM Universitas Putera Batam, 2023)
PT. ABCDE is a service company operating in the field of goods delivery and online purchases. Currently, PT. ABCDE aims to improve its services and quality standards in various aspects within the company, including the utilization of information technology. Currently, the existing services do not utilize a tracking application to obtain real-time information about the current location of the goods, causing a lack of transparency and inconsistencies in data across different departments. Additionally, the current process of generating delivery notes is manual, time-consuming, and leads to delays for drivers in delivering goods. Therefore, there is a need for a tracking application that records and displays real-time information about the current location of the goods, inputted by the drivers. Additionally, the application should automate the generation of delivery notes to reduce delays. This system will be designed using the PHP programming language and the Laravel framework, utilizing a MySQL server database that allows access from anywhere and anytime. The benefits obtained from this system include facilitating each department, especially the administrative team and owner, in checking the current location of the goods, and ensuring transparency of data across different departments to avoid any misinformation.